Tryptophan Intake and Tryptophan Losses in Hemodialysis Patients: A Balance Study - Post, Adrian (Nutrients, 2019)
Tryptophan depletion is common in hemodialysis patients. The cause of this depletion remains largely unknown, but reduced nutritional tryptophan intake, losses during dialysis or an increased catabolism due to an inflammatory state are likely contributors. Currently, little is known about tryptophan homeostasis in hemodialysis patients. We assessed dietary tryptophan intake, measured plasma tryptophan during dialysis, and measured the combined urinary and dialysate excretion of tryptophan in 40 hemodialysis patients (66 ± 15 years and 68% male). Patients had low tryptophan concentrations (27 ± 9 µmol/L) before dialysis. Mean dietary tryptophan intake was 4454 ± 1149 µmol/24 h. Mean urinary tryptophan excretion was 15.0 ± 12.3 μmol/24 h, dialysate excretion was 209 ± 67 μmol/24 h and combined excretion was 219 ± 66 µmol/24 h, indicating only 5% of dietary tryptophan intake was excreted. No associations were found between plasma tryptophan concentration and tryptophan intake, plasma kynurenine/tryptophan ratio or inflammatory markers. During dialysis, mean plasma tryptophan concentration increased 16% to 31 ± 8 µmol/L. Intradialytic increase in plasma tryptophan was associated with a lower risk of mortality, independent of age, sex and dialysis vintage (HR: 0.87 [0.76–0.99]; P = 0.04). Tryptophan intake was well above the dietary recommendations and, although tryptophan was removed during dialysis, mean plasma tryptophan increased during dialysis. The cause of this phenomenon is unknown, but it appears to be protective.